RELIABILITY LEVEL ON AFCS ACTUATOR COMPONENT OF THE SIKORSKY S-76 HELICOPTER - Aryanti Dwi Puspita; Sri Mulyani; Karseno KS (Institut Teknologi Dirgantara Adisutjipto, 2020)
The use of helicopters is very useful for Indonesia's natural conditions which is in the form of islands. In order to support the helicopter's capabilities, an AFCS actuator or automatic flight control system actuator is needed to make the flight automatically. Therefore, the author tries to conduct a reliability analysis to determine the level of reliability of the AFCS Actuator component in S-76 helicopter. The method used to conduct the analysis is the Weibull distribution method, which is one of several methods that are often used. The main objective is to determine the level of reliability and characteristics of the failure modes that often occur in these components. By analyzing at the results of calculations and types of failures, it can be seen the types of effective treatments to be applied to the AFCS Actuator component.